A bipolar homoleptic iridium dendrimer composed of diphenylphosphoryl and diphenylamine dendrons for highly efficient non-doped single-layer green PhOLEDs. Issue 5 (9th January 2015) - Tian, Wenwen; Qi, Qi; Song, Bo; Yi, Chang; Jiang, Wei; Cui, Xia; Shen, Wei; Huang, Bin; Sun, Yueming
Abstract : G2PO shows ultrahigh luminous efficiency for single-layer host-free green PhOLEDs, owing to the high film PLQY and balanced charge injection/transport. Abstract : A novel second-generation bipolar iridium(iii ) dendrimer featured with diphenylphosphoryl and diphenylamine groups has been designed and synthesized. A maximum current efficiency of 21.6 cd A −1 has been realized, which is among the highest ever reported for single-layer self-host green PhOLEDs.